2018
DOI: 10.1038/s41598-018-31196-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and microstructural study of Ti2AlNb oxides at 800 °C

Abstract: The high-temperature structural applications of Ti2AlNb-based alloys, such as in jet engines and gas turbines, inevitably require oxidation resistance. The objective of this study is to seek fundamental insight into the oxidation behavior of a Ti2AlNb-based alloy via detailed microstructural characterization of oxide scale and scale/substrate interface after oxidation at 800 °C using X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microanalysis (EPMA), and transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It is usually assumed that the interface satisfies the stabilizing relationship characteristics when the mismatch is less than 5%. The small interfacial mismatch degree also implies that the B2(110)/O(001) interface is basically coherent, which is often observed in Ti 2 AlNb alloys in experiments [14].…”
Section: Structural Modelsmentioning
confidence: 58%
See 1 more Smart Citation
“…It is usually assumed that the interface satisfies the stabilizing relationship characteristics when the mismatch is less than 5%. The small interfacial mismatch degree also implies that the B2(110)/O(001) interface is basically coherent, which is often observed in Ti 2 AlNb alloys in experiments [14].…”
Section: Structural Modelsmentioning
confidence: 58%
“…The oxidation process of Ti 2 AlNb alloys is controlled by the microstructure of the initial B2-O two-phase interface, and the extremely lamellar morphology restricts the diffusion of oxygen [13]. In our previous experiments on the oxidation mechanisms of Ti 2 AlNb alloys at 800 • C, the TEM observations revealed that the O phase and B2 phase followed a crystallographic-orientation relationship of [111]B2//[110]O and (110)B2//(001)O [14], which was also observed in other studies related to Ti 2 AlNb alloys [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even though the L-PBF process is carried out under an inert atmosphere, some oxygen pickup by the alloy is still possible due to high temperatures. It is also known that the diffusion of oxygen at the phase boundary is faster as a result of the presence of phase/grain boundary energy [52]. This results in increased oxygen content in the grain boundary O-phase leading to its further embrittlement.…”
Section: L-pbf Processabilitymentioning
confidence: 99%
“…In order to achieve the service requirements of modern aero-engines and further improve their various properties, the Ti 2 AlNb alloy was developed by adding Nb to the Ti 3 Al-based alloy [11,12]. The element Nb not only inhibits the oxidation of Ti, but also increases the activity of Al, enabling the alloy to preferentially produce stable Al 2 O 3 at high temperatures [13][14][15]. Therefore, Ti 2 AlNb alloy is expected to be the primary material used for making aero-engine hot-end components.…”
Section: Introductionmentioning
confidence: 99%